Abdominal epilepsy mimicking conversion disorder: a case report - Ozturk, Yusuf; Gol, Gueler; Savci, Ugur; Cansiz, Mehmet Akif; Tufan, Ali Evren (TAYLOR \& FRANCIS LTD, 2019)
In children and adolescents, especially younger ones, recurrent abdominal pains may develop as a response to psychosocial stressors. They may be considered as functional and be one of the common reasons for clinical referrals. A rare cause of recurrent, organic abdominal pain is abdominal epilepsy. Abdominal epilepsy may be considered in differential diagnosis of patients that were thought to have functional complaints. In this case, a 16-year-old adolescent girl whose chief complaints included loss of consciousness and recurrent abdominal pains lasting for a year is presented.
Keywords: Abdominal epilepsy; conversion disorder